Effect of short-term heat acclimation on endurance time and skin blood flow in trained athletes - Chen TI; Tsai PH; Lin JH; Lee NY; Liang MT (Dove Medical Press, 2013)
Tsung-I Chen,1,2 Pu-Hsi Tsai,3 Jui-Hsing Lin,4 Ning-Yuean Lee,5 Michael TC Liang61Graduate Institute of Sport Science, National Taiwan Sport University, Taoyuan, 2Center for Physical Education, Tzu Chi University, Hualien, 3Department of Sport and Leisure, National Quemoy University, Kinmen, 4Department of Physical Education, National Pingtung University of Education, Pingtung, 5College of Living Technology, Tainan University of Technology, Tainan, Taiwan; 6Department of Kinesiology and Health Promotion, California State Polytechnic University, Pomona, CA, USABackground: To examine whether short-term, ie, five daily sessions, vigorous dynamic cycling exercise and heat exposure could achieve heat acclimation in trained athletes and the effect of heat acclimation on cutaneous blood flow in the active and nonactive limb.Methods: Fourteen male badminton and table tennis athletes (age = 19.6 ± 1.2 years) were randomized into a heat acclimation (EXP, n = 7) or nonheat acclimation (CON, n = 7) group. For 5 consecutive days, the EXP group was trained using an upright leg cycle ergometer in a hot environment (38.4°C ± 0.4°C), while the CON group trained in a thermoneutral environment (24.1°C ± 0.3°C). For both groups, the training intensity and duration increased from a work rate of 10% below ventilatory threshold (VT) and 25 minutes per session on day 1, to 10% above VT and 45 minutes per session on day 5. Subjects performed two incremental leg cycle exercise tests to exhaustion at baseline and post-training in both hot and thermoneutral conditions. Study outcome measurements include: maximum oxygen uptake (VO2max); exercise heart rate (HR); O2 pulse; exercise time to exhaustion (tmax); skin blood flow in the upper arm (SkBFa) and quadriceps (SkBFq); and mean skin (Tsk).Results: The significant heat-acclimated outcome measurements obtained during high-intensity leg cycling exercise in the high ambient environment are: (1) 56%–100% reduction in cutaneous blood flow to the active limbs during leg cycling exercise; (2) 28% drop in cutaneous blood flow in nonactive limbs at peak work rate; (3) 5%–10% reduction in heart rate (HR); (4) 10% increase in maximal O2 pulse; and (5) 6.6% increase in tmax.Conclusion: Heat acclimation can be achieved with five sessions of high-intensity cycling exercise in the heat in trained athletes, and redistribution of cutaneous blood flow in the skin and exercising muscle, and enhanced cardiovascular adaptations provide the heat-acclimated athletes with the capability to increase their endurance time in the hot environment.Keywords: VO2max, oxygen pulse, skin blood flow, cardiovascular adaptation, badminton and table tennis players, short-term heat acclimation